STUDY OF THE PETROPHYSICAL CHARACTERISTICS OF ROCKS FROM THE LIBWA FIELD IN THE PINDA RESERVOIR IN THE D.R. CONGO COASTAL BASIN - André Yelembangu Ngwey; Jean Iyolo Lungembo; Dona Kampata Mbwelele; Gustave Ngalamulume Bantu; Néhémie Bikayi Tshiani; Rachidi Opuluku (Romanian Journal of Petroleum & Gas Technology)
The Libwa field, located offshore the Democratic Republic of Congo (DRC), has significant potential for hydrocarbon exploitation, particularly in the southern part, which remains unexploited. Previous studies have identified various hydrocarbon exploitation opportunities in place, as measured by the volumes of oil in place (STOIIP). However, recent analysis by Perenco DRC highlights the need for additional volumes to meet current production levels in the northern part of the field. The Pinda reservoir, which forms an essential part of the Libwa field, has a porosity of between 15% and 19%. However, it has a very low permeability, averaging less than 2 millidarcies (mD). This low permeability makes it difficult to accurately assess porosity using seismic data, due to minor variations in the geological structure. Ongoing research is aimed at gaining a better understanding of the geological structure of the Libwa field and determining whether additional volumes of hydrocarbons exist in the southern part or in other areas of the field. Understanding the petrophysical characteristics is crucial to optimizing extraction strategies and assessing the economic potential of the reservoir.